2019
DOI: 10.1038/s41598-019-41476-8
|View full text |Cite
|
Sign up to set email alerts
|

Life-long reduction in myomiR expression does not adversely affect skeletal muscle morphology

Abstract: We generated an inducible, skeletal muscle-specific Dicer knockout mouse to deplete microRNAs in adult skeletal muscle. Following tamoxifen treatment, Dicer mRNA expression was significantly decreased by 87%. Wild-type (WT) and Dicer knockout (KO) mice were subjected to either synergist ablation or hind limb suspension for two weeks. There was no difference in muscle weight with hypertrophy or atrophy between WT and KO groups; however, even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
6
33
0
Order By: Relevance
“…Our data showed that the muscle-enriched miRNAs were highly stable in the TA muscle of the iDicer KO mice (Figure 1B), which is consistent with our previous report [19]. Similarly, recent data on tamoxifen-inducible, skeletal muscle-specific Dicer knockout (HSA-MCM; Dicer fl/fl ) mice showed that the expression levels of miRNAs including miR-1, miR-133a and miR-206 were slightly affected by the Dicer depletion [32]. Several lines of evidence indicate that the mature miRNAs expressed in liver, heart, and neuron are also stable in vivo [33,34,35].…”
Section: Discussionsupporting
confidence: 90%
“…Our data showed that the muscle-enriched miRNAs were highly stable in the TA muscle of the iDicer KO mice (Figure 1B), which is consistent with our previous report [19]. Similarly, recent data on tamoxifen-inducible, skeletal muscle-specific Dicer knockout (HSA-MCM; Dicer fl/fl ) mice showed that the expression levels of miRNAs including miR-1, miR-133a and miR-206 were slightly affected by the Dicer depletion [32]. Several lines of evidence indicate that the mature miRNAs expressed in liver, heart, and neuron are also stable in vivo [33,34,35].…”
Section: Discussionsupporting
confidence: 90%
“…With these disadvantages in mind, and due to the specificity of new molecular and genetic indicators, their use becomes more and more appealing. As seen in Table 2, quite a few studies have highlighted the upregulation of the same four miRNAs, namely miR-1, miR-133a, miR-208a/b, and miR-499, shortly after myocardial infarction [59,[203][204][205], which are classically referred to as the myomiR family [206].…”
Section: Mirnas In Cardiovascular Diseasementioning
confidence: 99%
“…12 Our laboratory and others recently found that muscle-specific miRNAs (myomiRs) persist for prolonged periods in the absence of the miRNA processing enzyme Dicer. 13,14 If prolonged miRNA stability is a quality specific to skeletal muscle, 15 myomiRs could be good candidates as long-term epigenetic regulators of exercise adaptation, especially given their known function in regulating muscle mass. [16][17][18] In the current investigation, we provide evidence on myonuclear accretion and maintenance in skeletal muscles with different fibre type composition and function after 2 months of PoWeR training and prolonged 6-month detraining.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond myonuclear number, recent evidence suggests that DNA methylation changes in skeletal muscle induced by training could be long‐lasting and represent a memory of prior training exposure that facilitates future adaptation 12 . Our laboratory and others recently found that muscle‐specific miRNAs (myomiRs) persist for prolonged periods in the absence of the miRNA processing enzyme Dicer 13,14 . If prolonged miRNA stability is a quality specific to skeletal muscle, 15 myomiRs could be good candidates as long‐term epigenetic regulators of exercise adaptation, especially given their known function in regulating muscle mass 16–18 …”
Section: Introductionmentioning
confidence: 99%